2010
DOI: 10.1007/s00442-010-1632-2
|View full text |Cite
|
Sign up to set email alerts
|

Intra-tree variation in foliage quality drives the adaptive sex-biased foraging behaviors of a specialist herbivore

Abstract: Some herbivorous insects enhance their fitness using foraging strategies that allow them to find and colonize the best of available resources within heterogeneous plants. The yellowheaded spruce sawfly, Pikonema alaskensis (Roh.) (Hymenoptera: Tenthredinidae), is a common defoliator that oviposits and feeds on the developing foliage of young open-grown black spruce [Picea mariana (Mills) B.S.P.]. While female and male eggs are both laid throughout the crown, most eggs laid in the upper crown are female, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…For example, the spruce bud moth (Zeiraphera Canadensis Mutuura and Freeman), another tortricid that attacks young white spruce (Picea glauca (Moench) Voss), disperses acropetally so that it may feed twice on young foliage, Þrst in the lower crown where buds tend to burst Þrst and then in the upper crown where buds burst later (Quiring 1993). Similarly, the late-instar larvae of a tenthredinid sawßy, Pikonema alaskensis (Rohwer), also disperse acropetally to feed on more nutritious shoots in the upper crown of young spruce hosts (Johns et al 2009(Johns et al , 2010. Based on the L2 overwintering and subsequent defoliation patterns of other Choristoneura Nealis andLysyk 1988, Volney 1992), we suspect that these other species may also disperse acropetally in the spring, probably also by walking up the tree trunk.…”
Section: Results From Generalized Linear Models Assessing the Effecmentioning
confidence: 96%
“…For example, the spruce bud moth (Zeiraphera Canadensis Mutuura and Freeman), another tortricid that attacks young white spruce (Picea glauca (Moench) Voss), disperses acropetally so that it may feed twice on young foliage, Þrst in the lower crown where buds tend to burst Þrst and then in the upper crown where buds burst later (Quiring 1993). Similarly, the late-instar larvae of a tenthredinid sawßy, Pikonema alaskensis (Rohwer), also disperse acropetally to feed on more nutritious shoots in the upper crown of young spruce hosts (Johns et al 2009(Johns et al , 2010. Based on the L2 overwintering and subsequent defoliation patterns of other Choristoneura Nealis andLysyk 1988, Volney 1992), we suspect that these other species may also disperse acropetally in the spring, probably also by walking up the tree trunk.…”
Section: Results From Generalized Linear Models Assessing the Effecmentioning
confidence: 96%
“…Competition among kin and inbreeding avoidance can also produce sex-biased dispersal in mammals (Handley & Perrin 2007), birds [6], [10] and some fish species [11], [12], because competition among kin diminishes the inclusive fitness. Whether avoidance of kin competition can result in sex-biased dispersal is associated with the possibility that the two sexes compete for the same resources [13]. In polygamous mating systems, the breeding success of males may be limited mainly by the number of mating partners (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Johns et al. (), for instance, found that higher larval survival of a free‐feeding sawfly in the upper vs. lower crown of young black spruce, Picea mariana (Mill.) BSP, was correlated with 21% lower monoterpene content in the upper crown, despite only a 10‐mm difference in average length between the two crown levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study did not include foliar chemical analyses, several past studies have shown significant variation in insect performance and/or shoot nutritional chemistry among both crown levels and shoot types within young conifers. Johns et al (2010), for instance, found that higher larval survival of a free-feeding sawfly in the upper vs. lower crown of young black spruce, Picea mariana (Mill.) BSP, was correlated with 21% lower (Carroll & Quiring, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation